2017
DOI: 10.1080/08998280.2017.11929615
|View full text |Cite
|
Sign up to set email alerts
|

Review of Screening Studies for Atrial Fibrillation in Rural Populations of 11 Countries

Abstract: Atrial fibrillation (AF) is a common cardiac arrhythmia, and pathological burden can be influenced by environmental factors. The rural environment may influence the burden of AF, although no systematic review studies have been conducted to address this issue. We performed a systematic review of AF screening studies conducted in rural global populations to determine the burden, risk factors, and screening methods surrounding AF in these settings. Out of the 1792 articles gathered from a keyword search of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
3
1
Order By: Relevance
“…It is well established that significant racial differences exist, and rates of AF in Japan are much lower across all age groups, compared with representative data reported from Western countries. 12 13 It is therefore not surprising that the incidence rate of new AF for people aged ≥65 years is also lower in our study (~0.45%/year) than the rate of 1.4% in Western Countries, identified in a systematic review of screening. 14 It is thought that lower AF rates in Japan may be related to overall lower incidences of cardio-metabolic and other risk factors for AF, but over the next few decades, AF prevalence may increase with a gradual increase in lifestyle-related cardio-metabolic risk factors.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…It is well established that significant racial differences exist, and rates of AF in Japan are much lower across all age groups, compared with representative data reported from Western countries. 12 13 It is therefore not surprising that the incidence rate of new AF for people aged ≥65 years is also lower in our study (~0.45%/year) than the rate of 1.4% in Western Countries, identified in a systematic review of screening. 14 It is thought that lower AF rates in Japan may be related to overall lower incidences of cardio-metabolic and other risk factors for AF, but over the next few decades, AF prevalence may increase with a gradual increase in lifestyle-related cardio-metabolic risk factors.…”
Section: Discussioncontrasting
confidence: 42%
“… 14 It is thought that lower AF rates in Japan may be related to overall lower incidences of cardio-metabolic and other risk factors for AF, but over the next few decades, AF prevalence may increase with a gradual increase in lifestyle-related cardio-metabolic risk factors. 12 13 Therefore, the incidence of new AF in Japan may escalate in the future and will benefit from early detection. However, it is likely that many cases would not be detected without annual screening, as the majority (~73%) of our new AF cases were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with POAF were older compared to those who did not develop arrhythmia. Advanced age is, admittedly, a major risk factor for AF in patients in general 16,17 and in those undergoing cardiac surgery. 18,19 In fact, population aging, especially in emerging countries, will play an important role in changing the incidence of this type of arrhythmia in the general population, as well as in patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of AF screening studies conducted in rural settings acknowledged the need for more information on AF burden and risk factors specifically in rural areas. 27 In the Australian context, it is known that people living in rural areas have worse cardiovascular outcomes. 28 It has been reported that there is a lack of evidence about rural cardiovascular disease prevention and ‘characteristics associated with quality of care’, which highlights the need for more programmes in rural primary care, especially for high-risk patients.…”
Section: Introductionmentioning
confidence: 99%